Professional Identity Of A Non-Native Esol Teacher Performing In A Multilingual Country (2024)
Becoming an English teacher might be filled with challenges and obstacles, and living outside your country will add difficulty to this path. Everyone reacts and faces experiences differently. Nevertheless, it is essential to consider how facing unexpected circumstances reshapes one's identity and influences a teacher's personal and professional development. This narrative inquiry aims to present an autobiographical study of my experiences as an ESOL teacher living in Curacao through my bachelor's degree in teaching English as a foreign language at the Universityof Santo Tomas. It involves some of the most critical moments outside Colombia for a decade that have shaped my personal and professional identityand provided me with the skills, resilience, and strength to make this accomplishment possible. To complete this project, I have collected data through an autobiography and two journals in which I describe and reflect on stages of my life that I consider essential turning points in my career as an English teacher. By implementing the thematic analysis of the different narratives, I could identify the key elements that marked me during this period and how I dealt with the different challenges that have transformed me into the professional I am today. The results showed that most of these problematic experiences came from internal and personal issues rather than professional ones.